2016
DOI: 10.1002/eco.1775
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and sediment response to tree control and seeding on a high soil erosion potential site in Utah: evidence for reversal of an abiotic threshold

Abstract: Expansion of piñon (Pinus spp.) and juniper (Juniperus spp.) trees into semi‐arid sagebrush steppe may cause these systems to pass a biotic threshold into weed dominance and recurrent fire, as well as pass an abiotic threshold of accelerated soil erosion. To determine effects of chaining to reduce trees and seeding to increase vegetation cover, we measured runoff and sediment after natural precipitation on 10 m2 intercanopy runoff plots on untreated and treated areas over a 5‐year period. The former sagebrush … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 52 publications
(124 reference statements)
1
47
1
Order By: Relevance
“…Similar results were reported by Pierson et al (2007) following tree removal by cutting in a western juniper (J. occidentalis Hook.) The studies noted here demonstrate tree removal can be effective at recruiting understory cover and reversing the soil erosion feedback but that responses can be prolonged for substantially degraded cover conditions depending on the method of treatment (Pierson et al, 2007;Roundy et al, 2017;. Pierson et al (2007) reported increased intercanopy perennial herbaceous cover and litter cover 10 years after cutting juniper on a sagebrush shrubland in the later stages of woodland encroachment.…”
Section: Patch-scale Run-off and Erosion From Combined Processesmentioning
confidence: 84%
See 3 more Smart Citations
“…Similar results were reported by Pierson et al (2007) following tree removal by cutting in a western juniper (J. occidentalis Hook.) The studies noted here demonstrate tree removal can be effective at recruiting understory cover and reversing the soil erosion feedback but that responses can be prolonged for substantially degraded cover conditions depending on the method of treatment (Pierson et al, 2007;Roundy et al, 2017;. Pierson et al (2007) reported increased intercanopy perennial herbaceous cover and litter cover 10 years after cutting juniper on a sagebrush shrubland in the later stages of woodland encroachment.…”
Section: Patch-scale Run-off and Erosion From Combined Processesmentioning
confidence: 84%
“…However, our study does demonstrate tree removal on late-succession woodlands can effectively re-establish a "resource-conserving" vegetation structure and reverse the soil erosion feedback. In another Great Basin study, Roundy et al (2017) found that pinyon and juniper removal by chaining paired with a seeding treatment increased intercanopy vegetation cover from 5% to 24% 1 year after treatment and to more than 40% 3 years after treatment. woodland in the northwestern portion of the Great Basin.…”
Section: Patch-scale Run-off and Erosion From Combined Processesmentioning
confidence: 95%
See 2 more Smart Citations
“…A second step for ecological restoration is revegetation. This decreases water erosion by intercepting rainfall (Roundy et al, 2017;Tromble, 1987), increases water infiltration (Huang, Zhang, Hu, & Zhao, 2015;King, Franz, & Caylor, 2012;Piñol, Lledó, & Escarré, 1991), and promotes soil regeneration. Revegetation in quarry restoration is expected to enhance the establishment and survival of other new species through facilitation, which is an important mechanism of succession improvement in exposed soil surfaces (Clemente et al, 2004;Maestre & Cortina, 2004;Pugnaire, Haase, Incoll, & Clark, 1996).…”
mentioning
confidence: 99%